Tackling Nominal Chains in a Specialized Translation Classroom - Klabal, Ondřej; Kubánek, Michal (Research in Language, 2025)
Nominal chains are regarded as a feature of specialized discourse in English and their disambiguation as a challenge for translators and translation trainees. They occur in all types of specialized discourse and include legal terms, technical terms or institutional terms. In Czech the relations between the constituents need to be expressed more explicitly. The chapter draws on an experiment aiming to test how well translation trainees can decipher the relations between individual constituents of nominal chains and identify types of nominal chains most susceptible to wrong interpretation. Based on these results, this chapter discusses how the analysis of nominal chains may be supported in a specialized translation classroom and proposes a series of specific activities to the effect.